TAFSIR AYAT-AYAT MUSIBAH AHSIN SAKHO MUHAMMAD - Maemunah, Maya; Mursyid, Ali (Moderation | Journal of Islamic Studies Review, 2022)
The study of the interpretation of the verses related to disaster in this article is important for the reasons; First, the theme of disaster is always relevant, disaster always exists throughout human life. Second, Indonesia is a disaster-prone country. Third, these two years, there is still a prolonged Covid-19 outbreak. Fourth, born from the work of an Indonesian expert in the Qur'an, namely Dr. KH. Ahsin Sakho Muhammad, entitled "Tafsir Happiness" discusses the interpretation of the verses of calamity. The study is in the form of: (1) How is Ahsin Sakho Muhammad's interpretation of the verses of the Qur'an related to calamities and how to deal with them? (2) What are the sources of interpretation, interpretation methods, interpretation styles, and reference literatures in Ahsin Sakho Muhammad's Tafsir Happiness? (3) What is the relevance of Ahsin Sakho Muhammad's interpretation in the current era? From the discussion, it is described as follows: First, the interpretation of Ahsin Sakho Muhammad in Tafsir Happiness is a thematic interpretation which includes terms related to calamities, forms of disaster and calamity, factors that cause disasters and calamities and how to respond to disasters and calamities. . From the discussion, it was found that there were 11 terms related to disaster, namely; Mushibah, adh-Dhurr, ash-Sharr, al-'Adzab, as-Sayyi'ah, ar-Rijz, Naughty, Bala', alBa'sa, al-Wabal, and Fitnah. And there are 14 forms and calamities mentioned in the Qur'an. More specifically, there are 7 factors that caused the disaster. Meanwhile, to respond to it requires an attitude of patience, surrender and prayer (repentance). Second, the interpretation methodology in Tafsir Happiness is as follows; The source of the interpretation used is the interpretation of bi al-ma'tsur with the reference to his interpretation of the interpretation of at-Tabari, the interpretation of Ibn Kathir. alWasith, Mu'jam Mufahras li Alfazh Al-Qur'an, Mufradat fi Gharib Al-Qur'an and several others. The method used in Tafsir Happiness is the thematic method while the explanation is ijmali. For the pattern in the interpretation of happiness, namely the ijtima'iy style. Third, the interpretation of the verses of Ahsin Sakho Muhammad's disaster is very relevant considering that Indonesia is being hit by Covid-19, and it is very necessary to have patience, calm and self-examination (repentance).